Case Study of Aircraft Operational Noise Level Distribution Patterns at Zainuddin Abdul Madjid International Airport - Baiq Rema Junia Sasmita; Hilman Ahyadi; Lalu Muhammad Aby Dujana (Tinta Emas Institute, 2025)
Aircraft operational activities, especially in the airport area, are a major source of noise that can affect environmental comfort and health, including aircraft operations at Zainuddin Abdul Madjid International Airport. This study aims to determine the noise level due to aircraft operations and map the noise distribution pattern as a basis for environmental management planning. The method used in this research is a descriptive quantitative method. Measurements of noise and environmental conditions (wind speed, wind direction, and air humidity) were carried out at a distance of 0 m, 30 m,175 m, 300 m, 500 m, and 1 000 m. The noise level was measured using the Sound Level Meter (SLM) measuring instrument in decibel units. Analysis and mapping were done using Surfer 28 software. The results showed that the noise level ranged from 44 to 97 dBA. At a distance of less than 100 m, the noise level threshold value, as stipulated in the Minister of Environment Decree Number 48 of 1996. In addition, the resulting noise distribution shows a radial pattern. The radial pattern is characterized by the spread of sound that spreads from one point source in a circular manner, and the intensity tends to decrease as the distance increases.